DYNAMIC STABILITY ANALYSIS SOFTWARE DESIGN OF TUNNELING MACHINE BASED ON VB AND MATLAB - WEI Rui; JIN HeRong (Jixie qiangdu)
In order to ensure the stability of the tunneling machine system under various working conditions. The architecture of human-computer interaction interface module and computing module was designed. The three-dimensional cartesian coordinate system of the cutting arm was established,and the whole process spatial pose of the tunneling machine was represented based on the transformation of spatial pose matrix. The cutting load was calculated,a synthetic determination method for multiboundary stability was proposed. In addition,the program implementing process was formulated,and a longitudinal tunneling machine dynamic stability analysis software based on VB and MATLAB platform was developed. The software can be used to calculate cutting load,global stability,hinge force and torque in the tunneling process of tunneling machine under different working conditions,and the results can be outputted through the interface in the form of graphics or Excel table,which can provide references for the design of the tunneling machine and the selection of key parts.